Evaluation of the pharmacological treatment of arterial hypertension associated to heart failure in Camarones town. - Pedro Miguel Milián Vázquez.; Idalmis Pérez Alemán; Carlos Martín Álvarez; Maira Quirós Enríquez.; Lidia Vázquez Montero (Medisur, 2006)
Background: Arterial hypertension is a risk factor for many cardiovascular and cerebrovascular diseases. Objective: To evaluate the pharmacological treatment in patients with arterial hypertension, also suffering from heart failure. Methods: A descriptive-prospective study was carried out, this consisted in the use of prescription-indication drugs through a simple random sample study of 43 patients, representing the 35.2 % in six Family Clinical Units of the urban area of Camarones’ Communitarian Policlinic, Palmira, Cienfuegos, during the first semester of 2004. Results: the 51.2 % of the patients were included in the class II of the New York Heart Asociation’s classification, and the 55.8% were considered hypertense class II. The hypertensive drugs more used were the captopril and the clortalidone, and among the drugs associated to the hypertensive ones it was included the isosorbide dinitrate, the digoxin and the acetylsalicylic acid. The 87.3 % of the patients received a correct dose, and in the 88.9% it was followed an adequate administration interval. The prescription was considered adequate in the 65.1 % of the studied patients. Conclusions: the advances in the treatment of these diseases are due to different factors, even though the study shows that the treatment of the patient of the series is adecuate, it should be bettered as long as possible.